Current breakthroughs in the hardwood biorefineries: Hydrothermal processing for the co-production of xylooligosaccharides and bioethanol. (January 2022) - del Río, Pablo G.; Gullón, Beatriz; Wu, Jie; Saddler, Jack; Garrote, Gil; Romaní, Aloia
Highlights: Hydrothermal treatment was proposed as first stage of hardwood biorefinery. Hydrothermal treatment allows the biofuel production coupled with oligosaccharides. Hydrothermal treatment at high severity conditions improves enzymatic hydrolysis. Combined processes allow the integral valorization of hardwoods. The search for strategies that contribute to biorefinery feasibility is necessary. Abstract: The development of lignocellulosic biorefineries requires a first stage of pretreatment which enables the efficient valorization of all fractions present in this renewable material. In this sense, this review aims to show the main advantages of hydrothermal treatment as a first step of a biorefinery infrastructure using hardwood as raw material, as well as, main drawback to overcome. Hydrothermal treatment of hardwood highlights for its high selectivity for hemicelluloses solubilization as xylooligosaccharides (XOS). Nevertheless, the suitable conditions for XOS production are inadequate to achieve an elevate cellulose to glucose conversion. Hence, several strategies namely the combination of hydrothermal treatment with delignification process, in situ modification of lignin and the mixture with another renewable resources (concretely, seaweeds, and by-products generated in the food industry with high sugar content) were pinpointed as promising alternative to increase the final ethanol concentration coupled with XOS recovery in the hydrolysate.